Brainstem cavernous malformation - Estramiana, Ariel Roberto; Pinto de Santana, Diana Lara; Figueiredo, Eberval Gadelha; Teixeira, Manoel Jacobsen (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2013)
Cavernous malformation (CM) of the central nervous system (CNS) are acquired or developmental vascular malformations that represent the 5% to 15% of all vascular malformations of the CNS. Eighty to ninety percent of CM are supratentorial, 15% infratentorial, and 5% occur in the spinal cord. The subset of brainstem malformation presents as a very difficult paradigm for treating clinicians. The widespread use of magnetic resonance imaging (MRI) has increased the recognition of this disease. Clinical presentation, pathophysiology and treatment are discussed in this article.
Keywords: Central nervous system neoplasms; central nervous system; magnetic resonance imaging; cavernous malformation; cavernoma